Seismic vulnerability assessment of a Californian multi-frame curved concrete box girder viaduct using fragility curves. Issue 12 (1st December 2016) - Abbasi, Mohammad; Abedini, Mohammad Javad; Zakeri, Behzad; Ghodrati Amiri, Gholamreza
Abstract: Seismic response of multi-frame curved viaducts has been proved to be very complex due to typically inherent irregularities identified in this class of bridge structures such as deck in-plane curvature, altitudinal irregularity and deck discontinuity. The discontinuity provided by the expansion joint has made this class of bridges prone to catastrophic damages caused by multiple collisions between adjacent frames during both torsional and translational modes of responses as well as deck unseating at the expansion joints. This paper presents the seismic response of a Californian multi-frame curved concrete box girder viaduct, considering four different radii of curvature and five altitudinal coefficients, using fragility curves. Fragility curves are developed by considering different sources of uncertainties related to earthquakes, structural geometries and material properties. The full nonlinear time-history analyses are performed utilising 3-D numerical bridge models generated in OpenSees finite element platform. The results show that bridge vulnerability increases with increasing irregularity in bridge plan and elevation. It is observed that bridge components and system fragility show different sensitivity to each type and level of irregularity for each damage state. In addition, the obtained results can be used to aid seismic retrofit prioritisation, financial loss estimation, pre-earthquake planning and design improvement processes.